A Comparative Study between Postoperative Analgesia of Fascia Iliaca Compartment Block and Anterior Quadratus Lumborum Block in Proximal Femur Fracture - O. S. M. Abd Elmaksoud; S. E. M. Elansary; N. G. Fahmy; R. M. Hussien (Anesthesiology Research and Practice)
Elderly patients with various comorbidities are more likely to suffer from proximal femur fractures. It is also a painful fracture, and poor pain management can have serious physiological and psychological consequences, such as acute delirium. Purpose. The aim of this study is to compare the efficacy of ultrasound-guided transmuscular (anterior) quadratus lumborum block (QLB) versus infrainguinal fascia iliaca compartment block (FICB) in proximal femur fractures for postoperative analgesia. Patient-reported pain on the visual analogue scale (VAS), analgesic demand, and ambulation were the key factors. Patients and Methods. This prospective, randomised trial was done after receiving approval from the institute’ study ethical committee. In this study, ultrasound-guided infrainguinal fascia iliaca compartment block was compared to ultrasound-guided anterior quadratus lumborum block using 50 ml of bupivacaine 0.25%, with a maximum dose of 2.5 mg/kg at the end of surgery after spinal anaesthesia in 128 patients (64 patients in each group). Nalbuphine was given as rescue analgesia if VAS >3. Our 1st outcome was the first rescue analgesia and total analgesic consumption in the 1st 24 hours; the 2nd outcome was the time patients started to ambulate. Results. Postoperative pain perception was substantially greater in the FICB group starting from 30 min (P value 0.022) till 24 hours (P value <0.001), and they received a considerably larger total narcotic dose (14.1 ± 3.5) than patients in the QLB group (7.9 ± 3.4), P value (<0.001∗). The time required to achieve first rescue analgesia was much less in the FICB group (8.5 ± 2.2) compared to the QLB group (14.1 ± 4.5), P value (<0.001∗), and they took much longer to ambulate (22.3 ± 4.8) when compared to the QLB group (20.1 ± 4.6), P value (0.011∗). Hypotension (1.6%) was detected mainly in the QLB group, whereas poor fascial separation (1.6%) was observed only in the FICB group. There were no significant differences in complications between both the FICB and QLB groups. Conclusion. Patients receiving postoperative anterior QL block for proximal femur fracture demonstrated delayed first rescue analgesia and lower total nalbuphine consumption with early ambulation than patients who received FICB.